Legal Review Of The Implementation Of Castration Law On Sexual Crime Perpetrators In Indonesia - Randa Nainggolan; Kusno Kusno; Ahmad Ansyari Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to analyze the Implementation of Castration Law Against Sexual Crime Perpetrators in Indonesia. The type of research used in this writing is Normative Research, namely legal research conducted by examining library materials or secondary data. Discussion Results: The Implementation of Castration Law Against Sexual Crime Perpetrators in Indonesia has not been effectively implemented. This can be seen from the many cases of sexual crimes decided by judges, not containing additional criminal penalties in the form of castration for perpetrators of sexual crimes. In addition, the implementation of castration punishment for perpetrators of sexual crimes is still a pro and con for the community. Where the punishment is not in accordance with the criminal system regulated in the Criminal Code. Another reason that the implementation of castration punishment is unnecessary is because it clearly violates Law Number 39 of 2009 concerning Human Rights. Where perpetrators of crimes still have the opportunity to live and continue their descendants. Castration punishment is considered very cruel and cruel, and inhumane, even violating medical ethics.